A cadaveric study of anterior communicating artery - Sunitha Narayanan; G N Geetha (Wolters Kluwer Medknow Publications, 2021)
Background: Anterior communication artery is a collateral channel that connects the right and left anterior cerebral arteries in the circle of Willis. This helps in stabilizing the cerebral blood flow. Different types of variations of this artery were reported in the previous studies. The hemodynamic changes in the blood flow produced by variations induce strain at the sites of bifurcation, which may result in the formation of aneurysms. This commonly occurs at the meeting point of anterior communicating artery (ACoA) with the anterior cerebral artery. The anatomical variations in this portion may complicate the planning and performance of surgery which in turn will lead to postoperative complications. Materials and Methods: The study was conducted in 60 specimens of the brain in the department of anatomy, Government Medical college, Calicut. The artery was carefully dissected and observed. Photographs were taken. The observations were tabulated. Results: Variations were noted in 15 specimens (25%). Duplication of the artery was noted in 6 specimens (10%), hypoplasia in 3 specimens (5%), V-type artery in 1 specimen, and X-type in 6 specimens (10%). There was no triplication or plexiform type noted. An accessory anterior cerebral artery was noted in 3 specimens (5%). Conclusions: As the ACoA acts a collateral channel that stabilizes the cerebral blood flow, when there is any vascular occlusion in any components of the circle, the knowledge of these anatomical variations becomes significant. As the radiological and neurosurgical interventions are increasingly performed, nowadays, the surgeons and radiologists should be aware of these variations in the cerebral arteries.